Strategi Manajemen Dalam Pengembangan Sumber Daya Manusia Melalui Pendekatan Teoritis Dan Empiris Untuk Optimalisasi Kinerja Organisasi - Muhamad Arsy Trisdianto; Adianto Adianto; Resti Dewi Asturias (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
Human Resource Development (HRD) is a crucial aspect of organizational management, playing a key role in enhancing workforce productivity and ensuring business sustainability. In an increasingly competitive world, the role of strategic management in designing effective HR policies has become more vital. This study examines how strategic management approaches can be applied in HRD to improve overall organizational performance. The research employs a mixed-method approach, combining quantitative analysis through statistical techniques with qualitative analysis via surveys and interviews. The findings indicate that the integration of data-driven approaches in HR management significantly impacts employee retention, job satisfaction, and the effectiveness of training programs. By utilizing regression analysis, correlation, and predictive modeling, organizations can optimize recruitment strategies and workforce management based on industry trends and internal needs. Moreover, the study finds that companies adopting technology-based strategies in HR management show higher adaptability to changes in the business environment. The study concludes that implementing data-driven management strategies in HRD positively contributes to workforce efficiency and the achievement of organizational goals. Recommendations include strengthening predictive-based policies, investing in structured training programs, and developing digital HR systems to enhance workforce management effectiveness.